A strategy to teach business opportunities creation skills using information and communication technology - Donda, Lindelihle Pretty-Girl (University of the Free State, 2023)
This study aimed at designing a real-life-situation strategy of teaching business opportunities creation skills (BOCS), using information and communication technology (ICT). The strategy is developed against the background of several challenges impeding the teaching of BOCS using ICT in Amajuba District in KwaZulu-Natal (KZN). BOCS is one of the six purposes of Grade 12 Business Studies’ learning content which students must comprehend and apply in their real-life situations during and after exiting matric. When demonstrating BOCS, teachers should utilise strategies that empower students to see how to learn; look for new data; use new data; assess the significance of data; and tackle novel and non-course reading proficient issues, utilising ICT. This was discovered to be trying for most teachers, as they actually present exercises that show BOCS in a theoretical structure, which is taken out from their (students) application to information. This makes it hard for students to move and apply the information and their abilities to real-life circumstances due to for, example brief (short) class period which deny the infusion of theory and practice in the teaching of BOCS, particularly the entrepreneurial skills using ICT. Besides, ICT applications and portrayals during BOCS exercises are generally used to computerise conventional techniques for teaching and learning by teachers , as opposed to displaying and implementing the multifaceted nature of ICT. Because of these and different other issues, this exploration proposes a genuine circumstantial technique that will guarantee the implantation of a theory and practice that eventually empower students to apply the information and abilities procured in the homeroom to their genuine circumstance. The strategy further seeks to involve other external stakeholders aiming at forming an inter-sectoral and collaborative team with multiple and diverse entrepreneurial skills and knowledge required during the current Fourth Industrial Revolution (4IR) paradigm. It is undeniable that the 4IR has restructured the way we live, work, and interact with one another. This has led to radical changes in all the spheres of life including political, economic, social, education and social sectors (Elheddad, Benjasak, Deljavan, Alharthi, & Almabrok, 2021). It emerges on the previous digital revolution and capitalises on the synergistic effects of various advanced technologies (Jin & Shin, 2021), which includes the artificial intelligence, robotics, the internet of things, 3D printing, virtual and augmented reality. In the current study, the use of the 4IR enables teachers and students to use these technologies in the teaching of BOCS, the entrepreneurial skills in live share trading (Jin & Shin, 2021). For example, the use of robotics to execute trades. The investigation is grounded on bricolage, a hypothetical structure that was first and foremost presented by the French anthropologist, Levi-Strauss in the Savage Mind (1966). Bricolage identifies with the irregular and relates to the game as an erratic, accidental and additionally arbitrary outcome and is related with other objects, where different accessible materials, when recombined and additionally applied with new capacities, as well as different organisations, rediscovers another article (Campos & Ribeiro, 2016; Rogers, 2012). Additionally, participatory action research (PAR) has been applied to create information with the co-researchers. This standard was applied for its emancipatory propensities and in light of it relating with bricolage, as the two of them avow a variety of voices in the research. The researcher worked with a team of two Adult Education and Training (AET) teachers, four Grade 12 Business Studies learners, who are normally called Grade 13, as most of them repeat Grade 12, an Economic and Management Sciences (EMS) subject advisor, two entrepreneurs, a local economic development (LED) manager and two National African Federated Chamber of Commerce (NAFCOC) representatives. The study identified the challenges, strategies, conditions, threats and indicators, regarding the formulation of the real-life-situation strategy in the teaching and learning of BOCS, using ICT. Thereafter, we conducted a strength, weaknesses, opportunities and threats (SWOT) analysis amongst ourselves to determine our academic and personal identities. We also conducted a political, economic,social, technological, legal and environmental PESTLE analysis to awaken ourselves in terms of the macro-environments elements in which the study was conducted. The trading environments pertained the political, economic, social technological, legal and environmental elements learners were to analyse before executing the trade. The group's shared vision was to build a methodology that reacts to the difficulties impeding the teaching of BOCS utilising ICT in Amajuba District. The group held conversations in , workshops, and class perceptions (observations) with the aim of producing information that reacted to the goals of the examination (research). After multiple conversations, the research team agreed to single out one sub-topic from Investmrnt Securities, which was the live share trading using ICT. Fairclough's critical discourse analysis (CDA) was utilised to break down the desultory information. Information was dissected through three focal points, specifically the textual, discourse and social practice level.
Thesis (Ph.D.(Curriculum Studies))--University of the Free State, 2023
Keywords: Bricolage; Business opportunities creation skills (BOCS); Critical discourse analysis; Entrepreneurial skills and knowledge; Information and communication technology (ICT); Live share trading; Participatory action research (PAR)